Therapeutic role of gut microbiota in lung injury-related cognitive impairment - Cheng, Yanxia; Hu, Guangtao; Deng, Lin; Zan, Yalan; Chen, Xia (Frontiers in Nutrition, 2025)
Lung injury can lead to specific neurocognitive dysfunction, and the “triple-hit” phenomenon may be the key theoretical mechanism for the progressive impairment of lung injury-related cognitive impairment. The lung and brain can communicate biologically through immune regulation pathway, hypoxic pathway, neural circuit, mitochondrial dysfunction, and microbial influence, which is called the “lung-brain axis.” The gut microbiota is a highly complex community of microorganisms that reside in the gut and communicate with the lung via the “gut-lung axis.” The dysregulation of gut microbiota may lead to the migration of pathogenic bacteria to the lung, and directly or indirectly regulate the lung immune response through their metabolites, which may cause or aggravate lung injury. The gut microbiota and the brain interact through the “gut-brain axis.” The gut microbiota can influence and regulate cognitive function and behavior of the brain through neural pathway mechanisms, immune regulation pathway and hypothalamic–pituitary–adrenal (HPA) axis regulation. Based on the gut microbiota regulation mechanism of the “gut-lung axis” and “gut-brain axis,” combined with the mechanisms of cognitive impairment caused by lung injury, we proposed the “triple-hit” hypothesis. It states that the pathophysiological changes of lung injury trigger a series of events such as immune disorder, inflammatory responses, and microbiota changes, which activate the “lung-gut axis,” thus forming a “triple-hit” that leads to the development or deterioration of cognitive impairment. This hypothesis provides a more comprehensive framework for studying and understanding brain dysfunction in the context of lung injury. This review proposes the existence of an interactive tandem network for information exchange among the gut, lung, and brain, referred to as the “gut-lung-brain axis.” It further explores the potential mechanism of lung injury-related cognitive impairment caused by multiple interactions of gut microbiota in the “gut-lung-brain axis.” We found that there are many numerous pathophysiological factors that influence the interaction within the “gut-lung-brain axis.” The impact of gut microbiota on cognitive functions related to lung injury may be mediated through mechanisms such as the “triple-hit” hypothesis, direct translocation of microbes and their metabolites, hypoxic pathway, immune modulation, vagal nerve activity, and the HPA axis regulation, among others. As the research deepens, based on the “triple-hit” hypothesis of lung injury, it is further discovered that gut microbial therapy can significantly change the pathogenesis of the inflammatory process on the “gut-lung-brain axis.” It can also relieve lung injury and therapeutically modulate brain function and behavior. This perspective provides a new idea for the follow-up treatment of lung injury-related cognitive impairment caused by dysregulation of gut microbiota.